2019
DOI: 10.1177/1362361319890793
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of physical and mental health conditions in Medicare-enrolled, autistic older adults

Abstract: While there is emerging evidence on the prevalence of physical and mental health conditions among autistic adults, less is known about this population’s needs during older adulthood (aged 65+). We conducted a cross-sectional retrospective cohort study of 2016–2017 Medicare data to compare the prevalence of physical and mental health conditions in a national sample of autistic older adults (N = 4685) to a matched population comparison (N = 46,850) cohort. Autistic older adults had significantly greater odds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
188
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(226 citation statements)
references
References 40 publications
15
188
6
Order By: Relevance
“…Therefore, our results suggest that older adults with elevated autistic traits may be more susceptible to poorer mental, but not physical, health in later life. In the current study, elevated rates of almost all psychiatric diagnoses were observed in older adults with high vs low autistic traits; a pattern consistent with the literature on mental health in autistic adults (Croen et al, 2015;Hand et al, 2019;Lever & Geurts, 2016) and those with high autistic traits (Kanne, Christ, & Reiersen, 2009;S. Lundström et al, 2011).…”
Section: Table 4 / Physical Health Conditions Table Here Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Therefore, our results suggest that older adults with elevated autistic traits may be more susceptible to poorer mental, but not physical, health in later life. In the current study, elevated rates of almost all psychiatric diagnoses were observed in older adults with high vs low autistic traits; a pattern consistent with the literature on mental health in autistic adults (Croen et al, 2015;Hand et al, 2019;Lever & Geurts, 2016) and those with high autistic traits (Kanne, Christ, & Reiersen, 2009;S. Lundström et al, 2011).…”
Section: Table 4 / Physical Health Conditions Table Here Discussionsupporting
confidence: 91%
“…Lundström et al, 2011). For depression and anxiety diagnoses, a three to four-fold increase was found, comparable to the rates previously described in autistic adults across the adult life course (Croen et al, 2015;Hand et al, 2019), and in the few previous studies of older adults with high autistic traits (Geurts et al, 2016;Stewart et al, 2018). From self-rated current/recent symptoms, too, rates of anxiety and depression were elevated in the high autistic traits group; more than 20% passed clinical cut-off for depression and more than 10% for anxiety.…”
Section: Table 4 / Physical Health Conditions Table Here Discussionsupporting
confidence: 84%
See 3 more Smart Citations